Expressão de mucina e transportadores intestinais e perfil microbiano de pintainhos de diferentes linhagens desafiadas com Salmonella Enteritidis - Santos, Maylane Rayane Brito dos (2022)
The objective was to evaluate and compare the composition and diversity and expression of mucin and nutrient transporters in two chicken strains. Microbiome composition was investigated in birds of two strains by sequencing the 16S ribosomal RNA (rRNA) gene at 24, 96 and 168 hours after inoculation (hpi) with S. Enteritidis or sterile culture medium in two strains of chickens. Jejunal mucosa samples were collected for RNA extraction and later evaluation of the mucin gene (Muc2), the intestinal glucose transporters (Sglt1, Glut2 and Glut5) and the amino acid transporter (Asct1) and di-tripeptide transporter (PepT1) . According to the Shannon index, referring to the time after inoculation, it shows that the alpha diversity index is significantly lower in the treatments with 24h (P<0.05). The phyla Proteobacteria and Firmicutes were more dominant at 24, 96 and 168 hpi, there is greater abundance of Proteobacteria in relation to Firmicutes, the opposite occurs at 96 and 168 hpi. There was no significant effect at 24 hpi for intestinal transporters, however expression was upregulated for Muc2 in Label. In addition, there was lineage challenge interaction in the period of 168 hpi for Glut2. The strains apparently have different mechanisms in intestinal transport when challenged with S. Enteritidis.